The Sermon in the Habsburg Dynasty in Peru and their Relationship with the Genesis of the Modern State - Cristina Florez, Gloria (2010)
The Genesis of the Modern State in the West began in the late XIII Century and achieved its consolidation in the XVIII Century, it was needed to make certain changes and use several resources in order to legitimize the monarchical power. Among them stands out the intellectual dynamics, which includes aspects such as: images, speeches and political treaties as well as spectacles, civic and religious ceremonies. We have chosen among these resources some preaching examples given in Peru during the XVII Century and show the important role performed by sermons legitimating the Habsburg Dynasty in our territory